PENERAPAN DIGITAL MARKETING DALAM STRATEGI MENINGKATKAN UMKM - Afiq Yasfa; Suci Ramadhana (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
To promote products and services and identify potential new markets, digital marketers use digital media and tools such as social networks. Cyberspace is now able to connect people all over the world with each other and with devices. Micro, small and medium enterprises (MSMEs) are expected to help revive the economy amidst the current economic slowdown. Small and medium-sized businesses (SMEs) have a fighting chance if they adopt digital marketing strategies. To maximize profits, MSME players synergize in promotional media and digital distribution. Almost all micro, small and medium enterprises (MSMEs), as well as restaurants and fast food chains, now rely on digital marketing for advertising and distribution